Pelatihan Prenatal Yoga Sebagai Upaya Meningkatkan Kesehatan Fisik, Mental dan Emosional Ibu Hamil di Wilayah Puskesmas Kubutambahan I Bali - Widiastini, Putu monna Frisca; Lutfiana, Indrie; Sugiartini, Desak Ketut (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to improve the physical, mental, and emotional health of pregnant women through prenatal yoga classes. The method used consists of three stages: First, socialization and education are conducted by providing information on maintaining physical and mental health, as well as managing discomfort during pregnancy and the benefits of prenatal yoga. Second, prenatal yoga classes are conducted regularly with a licensed instructor. This class included physical exercises that are safe for pregnant women, breathing exercises (pranayama), and meditation techniques to help manage stress and anxiety. Third, an evaluation at the end of the program regarding physical, mental, and emotional changes is conducted using a questionnaire. The results showed a significant decrease in physical discomfort levels (t = 6.22, p = 0.0001), indicating that yoga can significantly reduce physical discomfort in pregnant women. Additionally, the duration of yoga (Î²1 = -0.3, p = 0.0002) and anxiety before yoga (Î²2 = -0.2, p = 0.015) had a significant effect in reducing physical discomfort after yoga. In contrast, the age of the pregnant women did not show a significant effect on physical discomfort after yoga (Î²3 = -0.03, p = 0.14). These findings suggest that the duration of yoga and better anxiety management contribute to the reduction of physical discomfort in pregnant women.